Thermal Effects on Compressive Strength of Local Limestone and Claystone - Ibrahim, Rahel K.; Ismail, Nawzat R.; Omar, Hemn M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Limestone and claystone are widely used in rocky mountainous areas as building materials in Kurdistan region, in particular, the city of Koya. The outbreak of fire in buildings will have a great impact on strengths of building materials. The property performance of these local materials is heavenly understudied. This research investigates the impact of high temperature on the physicomechanical properties of limestone and claystone from Fatha Formation in Koya in Kurdistan region of Iraq. For this purpose, cores were taken from intact rocks; their ends were cut by a mechanical saw to obtain a cylindrical shape and immersed in water for 24 h, and then, subjected to physicomechanical tests of specific gravity, water absorption, porosity, and uniaxial compressive strength. For determining the residual compressive strength, the specimens were taken out from water, surface dried, and exposed to high temperatures of 450, and 650°C for 2 h using an electric oven. The results showed that claystone specimens show more stable mechanical properties than the limestone after exposure to high temperatures, and the high temperature causes lightening in color and significant cracks in both materials.